Genetic markers in sheep meat breeding - A. V. Deykin; M. I. Selionova; A. Yu. Krivoruchko; D. V. Kovalenko; V. I. Truhachev (Вавиловский журнал генетики и селекции)
Cattle breeding, including sheep farming, is an important sector of agriculture. Increasing productivity and improving meat quality are considered today as the priorities in the industry. Significant advances have been achieved in sheep breeding through the use of genetics. The commonplace of all selection programs is using manufacturers selected on the basis of the quality of the offspring, relatives or ancestors. At the same time, using the achievements of molecular genetics can lead breeding to a new methodological level. The problem of finding reliable communication between productivity features and genetic markers has not yet been solved, because productivity is a set of features (unlike, for example, monogenic diseases) and its expression depends on the balance between various physiological functions. By contrast, imbalance may cause reduced productivity as a whole even if there is a positive role of prevailing element. Selection on the basis of genetic markers of productivity aims to work with animals with high genetic potential for weight gain and meat quality. This review considers promising genes – potential markers of productivity in sheep farming, such as growth hormone gene, callipyge, calpain and calpastatin, which have promise as genetic markers for sheep selection. However, it should be stated that in spite of numerous reports about potential genetic markers of productivity there is still no data about the influence of molecular genetic methods on improving the economic performance of sheep selection.